2015
DOI: 10.1111/acps.12442
|View full text |Cite
|
Sign up to set email alerts
|

The association between biological rhythms, depression, and functioning in bipolar disorder: a large multi‐center study

Abstract: Our study shows a dose-dependent association between the severity of depressive symptoms and degree of biological rhythms disturbance. Biological rhythms disturbance was also an independent predictor of functional impairment. Although the directionality of this relationship remains unknown, our results suggest that stability of biological rhythms should be an important target of acute and long-term management of bipolar disorder and may aid in the improvement of functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 42 publications
10
52
0
Order By: Relevance
“…Our results are consistent with those of other studies that have shown the functional impact of emotional dysregulation , sleep disorder , sexual dysfunction , and stigma in euthymic patients with BD.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with those of other studies that have shown the functional impact of emotional dysregulation , sleep disorder , sexual dysfunction , and stigma in euthymic patients with BD.…”
Section: Discussionsupporting
confidence: 93%
“…This may indicate that, among the temperaments assessed by the TEMPS-A, the cyclothymic temperament predisposes to disturbances in biological rhythms to the greatest extent. The correlation obtained with depressive temperament in BD subjects may corroborate the findings of a previous study by Pinho et al 13 that reported a dose-dependent association between severity of depressive symptoms and degree of biological rhythm disturbances, assessed by the BRIAN, in patients with BD.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies reported that biological rhythm disturbance was proportional to the intensity of depressive symptoms in BD, and both variables contributed to a poorer psychosocial functioning (Pinho et al, 2016). Variations of the biological rhythms are widely recognized as one of the most common warning signs in BD, being part of the diagnostic criteria for mood episodes (American Psychiatric Association, 2013;Harvey et al, 2009).…”
Section: Introductionmentioning
confidence: 99%